Pengaruh Penerapan Media Pembelajaran Interaktif Berbantu Assemblr Edu terhadap Hasil Belajar Aspek Kognitif pada Siswa Kelas IV MIS NU Palangka Raya: Effect of Implementing Interactive Learning Media Assisted by Assemblr Edu on Cognitive Aspect Learning Outcomes in Grade IV Students of MIS NU Palangka Raya - Jannah, Raudatul; Jasiah, Jasiah; Normuliati, Sri (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
This study is based on the fact that the cognitive learning outcomes of fourth-grade students of MIS NU Palangka Raya in the subject of Science are still relatively low, especially the material